Umestitev pravic odraslih bolnikov s celiakijo v slovenski pravni red - Zarli, Eva (Pravnik, 2024)
All rights that Slovenian law grants to patients with coeliac disease are limited exclusively to children up to the age of 18, or 26 in the case of those in education. The current situation, wherein adult coeliac patients receive no assistance from the state or the insurance community due to their disease, constitutes a violation of their right to healthcare. To regulate this field, the article assesses comparative legal regimes, broadly divided into four groups: 1) social assistance supplements, 2) flat-rate benefits, 3) benefits in kind, and 4) tax relief. It then confronts the question of which regime would be most appropriate for application within Slovenian legal framework. Although, at a theoretical level, the option of flat-rate benefits seems particularly attractive, the author concludes that due to the challenges of integrating such benefits into any area of social security law, the most appropriate alternative is to provide benefits in the form of tax relief.
Keywords: celiac disease; celiakija; compulsory health insurance; davčne olajšave; healthcare; obvezno zdravstveno zavarovanje; patients’ rights; pravice bolnikov; pravo socialne varnosti; Slovenia; Slovenija; social assistance; social security law; socialne pomoči; tax relief; zdravstveno varstvo